PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN CUSTOMER VALUE TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA PADA LOYALITAS NASABAH BANK BRI UNIT TIKU CABANG BUKITTINGGI - Nardiman, Nardiman (Jurnal Ekobistek, 2017)
This research aimed to find:1) the influence of customer relationship management on customer satisfaction, 2) the influence of customer value on customer satisfaction, 3) the influence of customer relationship management on customer loyalty, 4) the influence of customer value on customer loyality, 5 ) the influence of customer satisfaction on customer loyality at Bank BRI Unit Tiku Cabang Bukittinggi.The kind of research is expost-facto; the population research is customers of  Bank BRI Unit Tiku Cabang Bukittinggi, with totally are 2509 peoples. The withdraw of the sampling method is using  Accidental Sampling method, with total of sample are 118 peoples. Primary data was collected through polls using Likert Scale model that has been tested validity and reliability. Data analysis technique that was used is Path Analysis.The results of research are:1) there is a positive and significant impact for customer relationship management to customer satisfaction, 2) there is a positive and significant effect of customer value for customer satisfaction, 3) there is a positive and significant effect of customer relationship management for customer loyalty, 4) there is a positif and significant effect of customer value to customer loyalty, 5) there is a positive and significant effect of customer satisfaction to the customers loyalty at Bank BRI Unit Tiku Cabang Bukittinggi.In terms of directly or indirectly influence from customer relationship management, customer value, and satisfaction to customer loyalty of  Bank BRI Unit Tiku Cabang Bukittinggi is  22,75 %.It's meaning that understanding of customer relationship management has a direct role in the customer loyalty to Bank BRI Unit Tiku Cabang Bukittinggi. Keywors: Customer Relationship Management, Customer Value, Satisfaction, Loyality